HUBUNGAN KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) DENGAN KECELAKAAN KERJA PADA PEKERJA SEKTOR KONSTRUKSI RUMAH SAKIT BALI - Nataya, Stanita; Saputra, Adi; Saputra, Adi (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT A work accident is an unwanted incident or event that is detrimental to humans, damages property or losses to the work process. Cases of work accidents in the construction sector in Indonesia are 32%. The purpose of this study was to determine The Relationship Between Personal Protective Equipment With Accident Cases In Construction Workers of Hospital in Bali. Type of this research was quantitative analytics with a cross sectional design. The population was all construction of Hospital in Bali the number of 498 peoples. Sample of the respondents used convenience sampling tecnique. The instrument used was a questionnaire. Data analysis was conducted using univariate and bivariate (used Chi-square alternate test). The results of the analysis showed that there was a relationship between the use of safety helmets and work accidents in Bali Hospital construction workers (p = 0.011), but there was no relationship between the use of safety shoes and work accidents in Bali Hospital construction workers (p = 0.916). The suggestions given to the company include increasing supervision of the use of PPE for workers while the workers are in the project area, ensuring the availability of PPE is sufficient for all workers and the distribution of PPE to workers by subcontractors is carried out properly. Keywords: Compliance, Personal Protective Equipement (PPE), workplace accident